Planting Seeds of Victory: Creating Shared Meaning while Gardening amidst a Pandemic - Emma C. Cameron; Chandler R. Mulvaney; Erin Harlow; Tiare Silvasy; LuAnn Duncan; Heather Janney; Halie Corbett; Maxine Hunter; Amanda Marek; Mark Bailey (Journal of International Agricultural and Extension Education, 2021)
The Victory2020 Garden Community Program was established by faculty members within the University of Florida (UF), Institute of Food and Agricultural Sciences (IFAS) in Marion and Columbia County Extension offices. In response to COVID-19, the purpose of the program was to provide online-mediated programs that could be completed at the desired pace of the participants, while promoting a self-reliant, science-based approach to learning about home food production through gardening. Due to food insecurity rates in both Marion (14.4%) and Columbia (15.2%) counties ranking above the statewide average in Florida, an immediate need to provide educational resources on becoming self-sufficient in growing one’s own food became increasingly important due to nationwide supply-chain shortages (Feeding America, 2020). 2,548 participants representing 43 states and six countries were provided access to eight learning modules hosted by Canvas, an online tool through UF. Participants were provided a package of free seeds, including corn, squash, cucumber, and cowpea to plant their Victory2020 Garden. A purposeful online community was established by extension agents in Marion and Columbia counties to facilitate quality discussion and growth, culminating in over 225,000 total impressions. The findings of the program revealed that 88% of gardening households began eating more fruits and vegetables while 73% are embracing new food safety techniques in both the garden and kitchen. Primary investigators and co-pi's recommend an implementation of a program timeline to benefit the participants through diverse, online learning options. Continued programming addressing mental health, nutrition, and gardening is recommended across extension programs nationally
Keywords: Extension education; pandemic; Victory Garden; holistic wellness; social connection